Reliability and consistency analysis of markerless gait motion using a single camera - Yoon, J. S.; Park, S. H.; Han, S. J.; Chun, S. B.; Kim, B. S.; Joo, S. Y.; Eom, C. H.; Park, J. C. (Korean Journal of Sport Biomechanics, 2024)
Objective: The purpose of this study is to evaluate the clinical usability of markerless motion analysis by comparing single camera-based markerless motion analysis using computer vision and infrared camera-based motion analysis. Method: This study was conducted on five healthy adults (age: 28.60 ± 5.24 years, height: 172.10 ± 7.06 cm, weight: 73.10 ± 14.07 kg). A single camera was installed in the sagittal plane, and the subject walked a total of 6 m along a path three times at his own pace. Position data of the joint centers of the shoulders, hips, knees, ankles, and toes and angle data of the lower extremity joints were calculated and analyzed. Results: Joint center position data showed high agreement between methods for anterior-posterior and vertical movements, excluding medial-lateral movements. However, the reliability of markerless-based motion analysis showed lower reliability toward distal joints, and consistent errors were confirmed in medial and lateral movements. It was confirmed that the average error in the angle data of the lower extremity joints increased toward the distal joints. Conclusion: Research results show that single camera-based markerless motion analysis using computer vision is effective for forward, backward, and vertical motion when photographed in the sagittal plane. However, large errors occur in depth data between the subject and the camera, which can affect other biomechanical variables. Therefore, it is effective in terms of real-time analysis, easy setup, and low cost when using a single camera, but it is emphasized that supplementation with depth data is necessary for accurate analysis.